Manusia dan Pendidikan Perspektif Pendidikan Islam - Rozi, Bahru (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
Abstract In reality, human history can’t be separated from education. The purpose of this research is (1) knowing the substance of human education from islamic education perspective (2) knowing the relation between education and human quality from islamic education perspective (3) knowing the purpose of islamic education and also the pupose of human life. This research used library research method. The result of this research shows that: (1) substantially education is basic necessary and spesifically only can be done by human. (2) Education is the key of development, when the education quality is getting better, the quality of the society will get better too. (3) The purpose of islamic education does not separated from human life purpose, to build individuals as Allah worshippers who always fear of Him and can reach happy life in world and afterlife.